Analysis of common deafness gene mutations in deaf people from unique ethnic groups in Gansu Province, China. (September 2014) - Xu, Bai-Cheng; Bian, Pan-Pan; Liu, Xiao-Wen; Zhu, Yi-Ming; Yang, Xiao-Long; Ma, Jian-Li; Chen, Xing-Jian; Wang, Yan-Li; Guo, Yu-Fen
Abstract Conclusions: The GJB2 gene mutation characteristic of Dongxiang was the interaction result of ethnic background and geographical environment, and Yugur exhibited the typical founder effect. The SLC26A4 gene mutation characteristic of Dongxiang was related to caucasian backgrounds and selection of purpose exons, i.e. ethnic background and the penetrance of ethnic specificity caused the low mtDNA1555A>G mutation frequency in Dongxiang. Objectives: To determine the prevalence of GJB2 and SLC26A4 genes and mtDNA1555A>G mutations and analyze the ethnic specificity in the non-syndromic sensorineural hearing loss (NSHL) of unique ethnic groups in Gansu Province. Methods: Peripheral blood samples were obtained from Dongxiang, Yugur, Bonan, and ethnic Han groups with moderately severe to profound NSHL in Gansu Province. Bidirectional sequencing (or enzyme digestion) was applied to identify the sequence variations. Results: The pathogenic allele frequency of the three gene mutations was different. The frequency of the GJB2 gene among the Dongxiang, Yugur, Bonan, and ethnic Han groups was 9.03%, 12.5%, 5.88%, and 12.17%, respectively. No difference was found between the ethnic groups. The frequencies of the SLC26A4 genes were 3.23%, 8.33%, 0%, and 9.81%, respectively. The mutation frequency of mtDNA1555A>G was 0%, 0%, 0%, and 6.03%, respectively. No difference was found between the ethnic groups, except for the Dongxiang and ethnic Han groups, both in SLC26A4 gene and mtDNA1555A>G.